Frequency of Portal Vein Dilatation in Chronic Liver Diseased Patients through Ultrasound - Maneeza Ahmed, Sahar Khan, Habib Ullah, Atiq Ullah, Aqal Zaman, Rizwan Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cirrhosis is one of the chronic liver disease in which the liver cells get fibrose and healthy tissues converted into scar tissues. The scar tissues compress the sinusoidal space in which portal vein drains, this causes pressure in portal vein and due to the backflow of blood the portal vein dilates. Portal vein dilatation in chronic liver disease patients leads to various complications. The objective of this study was to find out the frequency of portal vein dilatation in chronic liver disease patients and correlate it with age, gender, smoking, spleen size and ascites. Methods: This cross-sectional study, which involves the convenient sampling techniquewas conducted at Shangla hospital Swat conducted in 2022 with sample size of 171 patients from World Health Organization calculator, out of 171 , 2 patients did not give response, so we included 169 patients.. confidence level taken is 95%. The level of significance is 5% and Prevalence is 20%. Data was collected through a standard and validated questionnaire which included three portions. 1st portion of questionnaire contained written informed consent. 2nd portion contained demographic profile of the patient. 3rdportion of questionnaire contained all the sonographic findings. Data were analyzed through SPSS version 22. Correlation, spearman and pearson tests were applied. Result: There were total of 169 patients consisted of 102 males and 67 females. Out of 169 patients 53 were having normal portal vein diameter and 116 were having portal vein dilatation. Portal vein diameter is not affected by gender. Age and smoking are associative factors of portal vein dilatation. Ascites occurs in chronic liver disease patients due to dilated portal vein. Portal vein dilatation does not affect spleen size. Early detection of liver diseases and diagnosis of focal and diffuse parenchymal disease can be made possible with ultrasound because its first line of investigation, its efficiency is 95%, its noninvasive, easily available in the backward areas and various factors such as liver size, shape changes, liver markings, echogenicity, nodular pattern, portal vein diameter, inferior vena cava irregularity and spleen size can all be timely detected with ultrasound and life can be saved. Conclusion: It is concluded in this study that portal vein dilatation increases with age and is more common in middle aged people, gender and spleen size does not show any relation with portal vein dilatation. Ascites increases with portal vein dilatation and smoking is also an associative factor for portal vein dilatation in chronic liver disease patients. Keywords: Chronic liver disease, ultrasonography, portal vein dilatation, portal hypertension, cirrhosis, parenchymal disease.